Formulaton of Nanoemulsion Biopesticide for Horticultural Plants from Fermented Extracts of Jongi Plant and Cigarette Butts - Lithamivitra, Lithamivitra; Aeni, Nurul; Miftah, Nurul; Kardinal, Kardinal; Reza, Abdul; Isdaryanti, Isdaryanti; Putera, Alexander Kurniawan Sariyanto; Nurdin, Gaby Maulida (Jurnal Biologi Tropis, 2024)
Pests are one of the major challenges faced by farmers, particularly those cultivating horticultural crops, due to the difficulty in eliminating these pests, which also increases production costs. Therefore, the development of a practical and effective biopesticide is essential. This study aims to develop a nanoemulsion biopesticide from two readily available raw materials, namely the jongi plant and cigarette butts. The research employed an in vitro laboratory testing method to evaluate the effectiveness of five formulas (F0, F1, F2, F3, and F4) against two types of pests, Fusarium sp. and whiteflies. The effectiveness was measured by the inhibition zone in the Fusarium sp. test and the mortality rate of whiteflies. Additionally, a direct toxicity test was conducted on tomato plants to assess the safety of the formula. The results showed that the developed biopesticide was effective in inhibiting the growth of Fusarium sp. compared to the positive control and increased the mortality rate of whiteflies. Among the four formulas tested, three of the best-performing formulas were selected based on their inhibition and pest mortality rates, followed by toxicity testing. Formula 3, composed of 0% tobacco, 70% jongi, 20% starter, and 10% palm sugar, with a final pH of 4.2, was found to be safe for use without causing side effects on the plants.